The role of microenvironment in stem cell-based regeneration of intervertebral disc - Chu, Genglei; Zhang, Weidong; Han, Feng; Li, Kexin; Liu, Chengyuan; Wei, Qiang; Wang, Huan; Liu, Yijie; Han, Fengxuan; Li, Bin (Frontiers in Bioengineering and Biotechnology, 2022)
Regenerative medicine for intervertebral disc (IVD) disease, by utilizing chondrocytes, IVD cells and stem cells, has progressed to clinical trials in the treatment of back pain, and has been studied in various animal models of disc degeneration in the past decade. Stem cells exist in their natural microenvironment, which provides vital dynamic physical and chemical signals for their survival, proliferation and function. Long-term survival, function and fate of mesenchymal stem cells (MSCs) depend on the microenvironment in which they are transplanted. However, the transplanted MSCs and the endogenous disc cells were influenced by the complicated microenvironment in the degenerating disc with the changes of biochemical and biophysical components. It is important to understand how the MSCs and endogenous disc cells survive and thrive in the harsh microenvironment of the degenerative disc. Furthermore, materials containing stem cells and their natural microenvironment have good clinical effects. However, the implantation of tissue engineering IVD (TE-IVD) cannot provide a complete and dynamic microenvironment for MSCs. IVD graft substitutes may need further improvement to provide the best engineered MSC microenvironment. Additionally, the IVD progenitor cells inside the stem cell niches have been regarded as popular graft cells for IVD regeneration. However, it is still unclear whether actual IVD progenitor cells exist in degenerative spinal conditions. Therefore, the purpose of this review is fourfold: to discuss the presence of endogenous stem cells; to review and summarize the effects of the microenvironment in biological characteristics of MSC, especially those from IVD; to explore the feasibility and prospects of IVD graft substitutes and to elaborate state of the art in the use of MSC transplantation for IVD degeneration in vivo as well as their clinical application.